La Guerra por el Control Estratégico en el Suroccidente Colombiano - Echandía Castilla, Camilo (Sociedad y Economía, 2004)
This paper intends to detect recent changes in the behavior of the war agents in the departments of Cauca, Huila, Nariño and Tolima, and the modification of the geography of conflict determined by these changes. The spatial distribution of armed activity corresponds decreasingly .to the stable presence of irregular groups, and increasingly to strategic objectives that are now more important than territorial control. What counts as a priority to strategic control are the advantages associated with war logic; therefore, the actions of armed organizations are oriented to the control of important corridors, of military zones for inroad and retreat, and of economic resources.